Effects of lifestyle intervention in BRCA1/2 mutation carriers on nutrition, BMI, and physical fitness (LIBRE study): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Kiechle, Marion; Engel, Christoph; Berling, Anika; Hebestreit, Katrin; Bischoff, Stephan; Dukatz, Ricarda; Siniatchkin, Michael; Pfeifer, Katharina; Grill, Sabine; Yahiaoui-Doktor, Maryam; Kirsch, Ellen; Niederberger, Uwe; et al.
Abstract Background Women with highly penetrantBRCA mutations have a 55–60 % lifetime risk for breast cancer and a 16–59 % lifetime risk of developing ovarian cancer. However, penetrance differs interindividually, indicating that environmental and behavioral factors may modify this risk. It is well documented that the risk for sporadic breast cancer disease can be modified by changing lifestyle factors that primarily include physical activity, dietary habits, and body weight. It can thus be hypothesized that the modification of these lifestyle factors may also influence the incidence and progression of cancer inBRCA mutation carriers. Methods/design This multicenter, interdisciplinary, prospective, two-armed, randomized (1:1) controlled trial aims to enroll a minimum of 600BRCA1 andBRCA2 mutation carriers to partake in either a lifestyle intervention or usual care. The study primarily aims to demonstrate an improvement of nutritional behavior (adherence to the Mediterranean diet), body mass index, and physical fitness. Furthermore, the effects on quality of life, stress coping capacity, breast cancer incidence, and mortality will be investigated. The intervention group (IG) will receive a structured lifestyle intervention over 12 months, whereas the control group (CG) will only receive information regarding a healthy lifestyle. During the first 3 months, women in the IG will receive structured, individualized, and mainly supervised endurance training with a minimum of 18 MET-h physical activity per week and nutrition education based on the Mediterranean diet. Over the following 9 months, IG monthly group training sessions and regular telephone contacts will motivate study participants. The CG will receive one general training session about healthy nutrition in accordance with the recommendations of the German Society of Nutrition (standard of care in Germany) and the benefits of regular physical activity on health status. At randomization and subsequent time points (3 and 12 months), cardiopulmonary fitness will be assessed by spiroergometry, and nutritional and psychological status will be assessed by validated questionnaires, interviews, and clinical examinations. Discussion As data on the role of lifestyle intervention in women with a hereditary risk for breast and ovarian cancer are currently lacking, this study will be of major importance from a scientific, as well as a practical advice viewpoint. It will investigate the optimal strategy to improve physical fitness, nutritional status, and psychological factors such as quality of life, perceived stress, optimism, as well as incidence and outcome of cancer in this selected group of women at high risk. If the study indicates a positive long-term outcome, a structured lifestyle intervention program could be added to health care prevention strategies forBRCA1 andBRCA2 mutation carriers. Trial registration ClinicalTrials.gov:NCT02516540 . Registered on 22 July 2015.